Pengaruh Audit Tenure, Rotasi Audit, dan Fee Audit terhadap Kualitas Audit - Tasya Hervia Dewita; Erinos NR (Universitas Negeri Padang, 2023)
This research aimed to examine the effect of audit tenure, audit rotation, and audit fee on audit quality. The population in this research are all property, real estate, and building construction sector companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique used the purposive sampling. Total sample are 111 companies. The statistical method used logistic regression analysis. The result showed that audit tenure and audit rotation had a negative effect on audit quality, and audit fee had no significant effect on audit quality in property, real estate, and building construction sector companies listed on the Indonesia Stock Exchange in 2018-2020.